Skill elements for faster racing times - Rushall, B. S.
This article has been adapted from NSWIMMING Coaching Ssience Bulletin: Volume 1 Number 2 - September, 1992. It's content: 1.Introduction 2.Starts Teaching starts Backstroke starts Teaching the backstroke underwater action 3.Turns Basic principles Teaching turns 4.Finishes Teaching finishes 5.Learning Non-swimming Skills 6.Training Non-swimming Skills 7.Closoure 8.References